Enhancing the functionality of self-assembled immune signals using chemical crosslinks - Ackun-Farmmer, Marian; Jewell, Christopher M. (Frontiers in Immunology, 2023)
Multiple sclerosis (MS) is an autoimmune disease that develops when dysfunctional autoreactive lymphocytes attack the myelin sheath in the central nervous system. There are no cures for MS, and existing treatments are associated with unwanted side effects. One approach for treating MS is presenting distinct immune signals (i.e., self-antigen and immunomodulatory cues) to innate and adaptive immune cells to engage multiple signaling pathways involved in MS. We previously developed immune polyelectrolyte multilayer (iPEM) complexes built through layer-by-layer deposition of self-antigen - myelin oligodendrocyte glycoprotein (MOG) - and toll-like receptor antagonist, GpG to treat MS. Here, glutaraldehyde-mediated stable cross-links were integrated into iPEMs to load multiple classes of therapeutics. These cross-linked iPEMs maintain their immunological features, including the ability of GpG to blunt toll-like-receptor 9 signaling and MOG to expand T cells expressing myelin-specific T cell receptors. Lastly, we show that these functional assemblies can be loaded with a critical class of drug - mTOR inhibitors - associated with inducing regulatory T cells. These studies demonstrate the ability to incorporate small molecule drugs in reinforced self-assembled immune signals juxtaposed at high densities. This precision technology contributes new technologies that could drive antigen-specific immune response by simultaneously modulating innate and adaptive immunity.